FORMATION OF THE CONTROL SUBSYSTEM OF STRATEGIC INDICATORS OF COMPETITIVE ADVANTAGES OF THE ENTERPRISE - HROMOVA, Olha; SHARKO, Vitalii (Herald of Khmelnytskyi National University. Economic sciences, 2022)
In the article, the interpretation of holisticness in the structural model of marketing strategic management of the competitiveness of the enterprise is formed. The functional content of marketing strategic management of competitiveness in the management system of a machine-building enterprise is substantiated. The functional interrelationships of the company’s divisions in the strategic management of competitiveness are interpreted. Functional stages in the subsystem of evaluating the competitiveness of the enterprise are proposed. An interpretation of the interaction of the structural elements of the marketing strategic management system in increasing the competitiveness of an industrial enterprise based on a holistic approach to management processes is offered. Economic parameters are grouped for monitoring the level of marketing and strategic support of competitiveness of industrial enterprises. The functional differences of the subsystem of controlling, monitoring and control in the system of managing the competitiveness of the enterprise are determined. The correspondence of the principles of the subsystem of controlling the level of competitiveness of the enterprise and the system of marketing strategic management is presented. The level of influence of diagnostics in marketing strategic management on improving the functioning of the controlling subsystem is substantiated. A model of the subsystem for controlling the level of competitiveness of an industrial enterprise is proposed. The conditions of improvement and functioning of the subsystem of control of the level of competitiveness of an industrial enterprise are detailed. The author provided recommendations on the implementation of the control subsystem of the level of competitiveness of an industrial enterprise into the management system.